Hook Wire Localization of Pulmonary Pure Ground-Glass Opacities for Video-Assisted Thoracoscopic Surgery - Huang, Weizhao; Ye, Hongyu; Wu, Yingmeng; Xu, Wei; Tang, Xuan; Liang, Yi; Zheng, Junmeng; Jiang, Haiming (The Thoracic and Cardiovascular Surgeon, 2014)
Objective We compared the success of preoperative hook wire localization of pulmonary pure ground-glass opacities (pGGOs) with intraoperative palpation during video-assisted thoracoscopic (VAT) surgery and examined the safety of the preoperative hook wire method.Methods A total of 39 patients with 41 pulmonary pGGOs less than 2 cm in diameter underwent preoperative hook wire localization guided by DSA Innova CT before VAT lesion resection. The relationship between localization, as determined by finger palpation or hook wire, and clinicopathological factors was analyzed retrospectively. Complications resulting from hook wire localization are summarized.Results Twelve lesions (29.3%) were successfully identified by palpation, whereas 39 (95.1%) were successfully identified by hook wire (p < 0.01). The hook wire was dislodged in three cases (7.3%). No correlation was found between the positive rate of finger palpation or hook wire localization and the size, depth, position, or pathological grade of the lesion. Following surgery, five patients (12.8%) had asymptomatic minimal pneumothoraces, two patients (5.2%) had minimal hemothorax, and one patient (2.6%) had serious chest pain.Conclusions Preoperative localization of pulmonary pGGOs is necessary for VATS when the lesions are less than 2 cm in diameter. Preoperative hook wire localization is safe and more successful than palpation for localization of pGGOs.
Keywords: hook wire; pure ground-glass opacity; localization; video-assisted thoracoscopic surgery